Fate of Enterotoxigenic Staphylococci in Fish Subjected to Curing - S., Sanjeev; P.K., Surendran (Fishery Technology, 2025)
Enterotoxin A,B/C,D and E producing strains of Staphylococcus aureus were innoculated into dressed Barracuda fish (Sphyraem sp.) salted (3:1) for 48 h and dried in the sun for 3 days. The total bacterial count, S. aureus count and moisture content decreased after 48 h salt curing and decreased further after sun drying. S. aureus could not be isolated after 3 days of sun drying from the fish.